2007
DOI: 10.1111/j.1530-0277.2007.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Impairment of Hippocampal Neurogenesis in Young Adult Rats Following Early Postnatal Alcohol Exposure

Abstract: These observations suggest that early postnatal binge alcohol exposure results in long-term deficits of adult hippocampal neurogenesis, providing a potential basis for the deficits of hippocampus-dependent behaviors reported for this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
137
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(162 citation statements)
references
References 84 publications
21
137
3
1
Order By: Relevance
“…Impairment in memory (e.g., problems remembering information learned recently; repeatedly making the same mistakes; difficulty remembering long verbal instructions) 5. Impairment in visual spatial reasoning (e.g., disorganized or poorly planned drawings or constructions; problems differentiating left from right; problems aligning numbers in columns) hippocampal volume have been linked to functional memory impairments in human neuroimaging studies [41,42] and animal models [39,43]. Active working memory, which involves the capacity to store and process meaningful units at a given moment in time, has been found to be deficient in individuals with PAE, particularly for tasks involving multiple-step instructions [31].…”
Section: Memory Deficitsmentioning
confidence: 99%
“…Impairment in memory (e.g., problems remembering information learned recently; repeatedly making the same mistakes; difficulty remembering long verbal instructions) 5. Impairment in visual spatial reasoning (e.g., disorganized or poorly planned drawings or constructions; problems differentiating left from right; problems aligning numbers in columns) hippocampal volume have been linked to functional memory impairments in human neuroimaging studies [41,42] and animal models [39,43]. Active working memory, which involves the capacity to store and process meaningful units at a given moment in time, has been found to be deficient in individuals with PAE, particularly for tasks involving multiple-step instructions [31].…”
Section: Memory Deficitsmentioning
confidence: 99%
“…These effects are likely the direct result of cell death in the brain. Several studies have used various alcohol exposure paradigms in rodents to find that ethanol causes robust cell death in multiple brain regions during the first week of postnatal life [82][83][84][85][86]. Notably, none of these seminal studies examined alcohol-induced cell death in females.…”
Section: Alcoholmentioning
confidence: 99%
“…Current understanding of spatial memory deficits in children with FASDs is largely derived from an extensive animal literature showing that rats exposed to ethanol during early brain development had impaired place learning ability (Gianoulakis, 1990;Sutherland et al, 2000) and damage to the hippocampus (Klintsova et al, 2007;Livy et al, 2003), an area closely associated with spatial learning and recall and particularly vulnerable to alcohol exposure in animals and humans (Berman & Hannigan, 2000). In a study of three children who sustained early bilateral hippocampal damage due to hypoxic-ischemic brain injury, VarghaKhadem et al (1997) found significant impairments in delayed reproduction of a spatial arrangement using the Rey-Osterrieth Complex Figure task (ROCF) and poor everyday spatial memory using the parental report Everyday Memory Questionnaire (EMQ).…”
Section: Introductionmentioning
confidence: 99%